Emergence of Linezolid Resistance Genes optrA and cfr(D) in an Enterococcus saccharolyticus from Chicken - Xun Gao; Xiao Luo; Ruorou Qian; Guolong Gao; Jinghao Liu; Junhao Hong; Chao Yue; Jian-Hua Liu; Yi-Yun Liu (Antibiotics)
Background: The emergence of linezolid resistance, mediated by genes such as optrA and cfr(D), poses a growing public health threat. While these genes have been detected in clinical and animal-derived Enterococcus species, their presence in underexplored species like Enterococcus saccharolyticus remains undocumented, leaving a significant gap in our understanding of their dissemination and stability. Method: E. saccharolyticus GXN23C125Es was screened for the presence of known linezolid resistance genes via PCR analysis. Conjugation and stability experiments were used to evaluate the transferability and stability of the resistance genes. The complete genome of GXN23C125Es was obtained using both the Illumina and Nanopore platforms. Results: We report the first identification of optrA and cfr(D) in GXN23C125Es from chicken feces in China. Whole-genome sequencing revealed multiple plasmid-borne resistance genes, including optrA, cfr(D), fexA, and erm(A). Stability testing demonstrated that optrA was highly stable, while cfr(D) was rapidly lost without selective pressure. Conclusions: These findings highlight E. saccharolyticus as a potential reservoir for linezolid resistance genes, underscoring the need for enhanced surveillance of resistance determinants in animal-associated bacteria. Understanding the dissemination dynamics of optrA and cfr(D) is crucial for mitigating their impact on public health and guiding antimicrobial resistance management strategies.